Data for "Regenerated Cellulose & Willow Lignin Blends as Potential Renewable Precursors for Carbon Fibers" - Rahatekar, Sameer S.; Wanasekara, Nandula; Eichhorn, Stephen; Harniman, Robert (Cranfield University, 2018)
Data to support figures in the accompanying paper.
Keywords: 'Cellulose'; 'Lignin'; 'Fiber SpinningThis work reports'; 'ionic liquids'; 'carbonization'; 'carbon fibers'; 'Composite and Hybrid Materials'; 'Biomaterials'